The Effectiveness of KATAJAGA Health Education on the Changes of Knowledge, Attitudes, and Behavior of Defecation of Community in Tambakromo Bojonegoro (Universitas Negeri Semarang, 2021)
Practicing open defecation is a health and social problem that needs immediate attention. About 17 percent of households in 2010 or around 41 million people still defecated in the outside rather than in toilet. The purpose of this study was to determine the effectiveness ofÂ Total Family Latrine Village (KATAJAGA) health education on the changes of knowledge, attitudes and behavior of defecating in the community in Tambakromo Bojonegoro. This study applied a quantitative research with a quasy experimental research method by using pre-post-test with control group design. The sample in this study consisted of 236 respondents representing the intervention group and the control group conducted by using a purposive sampling technique. The instrument used in this study was a questionnaire and observation sheet. The data collection techniques were interviews, pre-test and post-test. The data analysis in this study was done by using Mann Whitney to determine the differences between the experimental group and the control group. The results of the study showed that there was an effective effect of giving Total Family Latrine Village (KATAJAGA) education on the changes in knowledge (p = 0,000), attitudes (p = 0,000), and behaviour (p = 0,000) of defecation. There were differences between the intervention and control groups in Tambakromo Bojonegoro community, it can be seen from the p value is 0.05. Efforts to improve the environmental sanitation and basic sanitation conditions in East Java were carried out by using Community-Based Total Sanitation (STBM).